The Influence Of Brand Image and Brand Ambassadors On Purchasing Decisions At Tokopedia In Purwakarta - Marlina, Ropi; Hidayati, Ashri; Sari, Juliani Lisma; Firmansyah, Muhammad Irfan; Wahyudi, Robby; Novian, Mardani (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
Keywords:Brand Image, Brand Ambassador, Purchasing Decision Abstract : This research was conducted with the aim of finding out the influence of brand image and brand ambassadors on purchasing decisions at Tokopedia in Purwakarta. The method used in this research is a descriptive method with a quantitative approach. The sampling technique used a non-probability sampling method with a purposive sampling technique with a total of 97 respondents. The data analysis used in this research is multiple linear regression analysis using IBM SPSS 25. The results of this research show that: 1) Brand Image has a positive and significant effect on purchasing decisions at Tokopedia; 2) Brand Ambassadors have a positive and significant influence on purchasing decisions at Tokopedia; 3) Brand Image and Brand Ambassador simultaneously influence purchasing decisions. Brand Image and Brand Ambassador have an influence of 78.